2005
DOI: 10.1093/carcin/bgi049
|View full text |Cite
|
Sign up to set email alerts
|

22-Oxa-1α,25-dihydroxyvitamin D 3 inhibits metastasis and angiogenesis in lung cancer

Abstract: 1alpha,25-Dihydroxyvitamin D(3) (1alpha,25-D(3)) has potent antiproliferative and anti-invasive properties in vitro in cancer cells. However, its calcemic effect in vivo limits its therapeutic applications. Here, we report the efficacy of 22-oxa-1alpha,25-dihydroxyvitamin D(3) (22-oxa-1alpha,25-D(3)), a low calcemic analog of vitamin D, against the development of metastatic lung carcinoma after an intravenous injection of green fluorescent protein-transfected Lewis lung carcinoma (LLC-GFP) cells in C57BL/6 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 39 publications
4
98
0
Order By: Relevance
“…The antitumor activity of 22-oxa-D 3 was more obvious in our mouse model than in cell cultures. The enhancement of 22-oxa-D 3 activity and its role in suppressing tumor growth in vivo can be explained by the finding that, apart from inducing cell cycle arrest as a result of enhanced expression of the cyclin-dependent kinase inhibitors p21 WAF1 and p27 Kip1 , 23,24 , a variety of mechanisms, including the regulation of angiogenesis, 25 increased apoptosis, 26 and reduced tumor invasiveness, 25,27 reportedly responsible for the actions of 1,25(OH) 2 D 3 . These latter 3 mechanisms could not be demonstrated in our CCA cell culture studies.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of 22-oxa-D 3 was more obvious in our mouse model than in cell cultures. The enhancement of 22-oxa-D 3 activity and its role in suppressing tumor growth in vivo can be explained by the finding that, apart from inducing cell cycle arrest as a result of enhanced expression of the cyclin-dependent kinase inhibitors p21 WAF1 and p27 Kip1 , 23,24 , a variety of mechanisms, including the regulation of angiogenesis, 25 increased apoptosis, 26 and reduced tumor invasiveness, 25,27 reportedly responsible for the actions of 1,25(OH) 2 D 3 . These latter 3 mechanisms could not be demonstrated in our CCA cell culture studies.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, vitamin D down-regulates the activity of NF-KBETA activity [242] and stimulates anti-inflammatory cytokines [239,243]. Additionally, vitamin D-binding proteins are more evident in proximity to endothelium injury [244], inhibiting the expression of MMP-2, MMP-9 and of the endothelium growth factor [245]; they probably diminish the activity of platelet derived growth factor, conversely up-regulating thrombomodulin [246][247]. The second study, entirely dedicated to small vessel disease and vitamin D [224] lights some shadows in a fascinating problem: it presents a well-known association between bone small vessel disease and osteoporosis.…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Animal and in vitro studies have shown that vitamin D can suppress tumor progression by reducing cell proliferation, invasiveness, and angiogenesis and stimulating apoptosis and cell differentiation (3)(4)(5). It has also reported to protect against metastasis in various tumor models, including cancer of the lung (3,5).…”
Section: Introductionmentioning
confidence: 99%